2020
DOI: 10.3390/ma13040913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Trace Addition of Sn on the Aging Behavior of Al–Mg–Si Alloy with a Different Mg/Si Ratio

Abstract: In this paper, the effect of trace Sn on the precipitation behavior and mechanical properties of Al–Mg–Si alloys with different Mg/Si ratios aged at 180 °C was investigated using hardness measurements, a room-temperature tensile test, transmission electron microscopy and differential scanning calorimetry. The results shown that Sn reduces the precipitation activation energy, increases the number density of β″ precipitates, and then increased the aging hardenability and mechanical properties of the Al–Mg–Si all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…15 A similar observation was also reported by Zhang et al 16 and further the authors concluded that at an artificial ageing temperature of 180 °C, the effect of Sn on age hardness depends on the composition of the Al-Mg-Si alloy. It was also reported 17 that in Mg-rich Al-Mg-Si alloy (Mg/Si = 1.7) at an ageing temperature of 180 °C, Sn (0.1 wt%) increases the number density of b 00 precipitate and improves the mechanical properties, whereas in Si-rich Al-Mg-Si alloy (Mg/Si = 0.58) at ageing temperature of 180 °C, Sn (1.1 wt%) weakens the strengthening effect of the b 00 precipitate and thereby decreases the mechanical properties of the Al-Mg-Si alloy. A similar observation was reported by He et al 18 in Si-rich Al-Mg-Si alloy (Mg/Si = 0.92) containing a high amount of Sn (0.4 wt%).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…15 A similar observation was also reported by Zhang et al 16 and further the authors concluded that at an artificial ageing temperature of 180 °C, the effect of Sn on age hardness depends on the composition of the Al-Mg-Si alloy. It was also reported 17 that in Mg-rich Al-Mg-Si alloy (Mg/Si = 1.7) at an ageing temperature of 180 °C, Sn (0.1 wt%) increases the number density of b 00 precipitate and improves the mechanical properties, whereas in Si-rich Al-Mg-Si alloy (Mg/Si = 0.58) at ageing temperature of 180 °C, Sn (1.1 wt%) weakens the strengthening effect of the b 00 precipitate and thereby decreases the mechanical properties of the Al-Mg-Si alloy. A similar observation was reported by He et al 18 in Si-rich Al-Mg-Si alloy (Mg/Si = 0.92) containing a high amount of Sn (0.4 wt%).…”
Section: Introductionmentioning
confidence: 72%
“…11,12 The effect of alloying Sn on the mechanical properties of the Al-Mg-Si alloy very much depends on the Mg/Si ratio and the ageing temperature. [13][14][15][16][17][18] At pre-aged (110 °C) and paint bake (165 °C) conditions, the negative effect of Sn (0.04 wt%) on the mechanical properties in high Mg-rich Al-Mg-Si alloy (Mg/Si = * 2) was observed by Glockel et al 14 However, the simultaneous addition of Zn (3 wt%) and Sn was found to prevent the negative effect and significantly improve the mechanical properties of the alloy. This was because Sn suppresses Mg-Si co-cluster formation, whereas Zn promotes Mg-Si co-cluster formation.…”
Section: Introductionmentioning
confidence: 98%
“…It was also observed that Zinc addition eliminates the negative effect of Sn addition in the properties of high magnesium content 6000 Al alloy [6]. Sn addition in 6000 alloys had been also shown as a potential accelerating artificial age hardening agent [7][8][9]. He et.…”
Section: Introductionmentioning
confidence: 96%
“…Alloying elements like Mg and Si in 6000 alloys reduce the dislocation motion through formation of hardening Mg 2 Si precipitates, thereby increasing the mechanical strength [4]. Sn in 6000 Al alloys is a potential trace element [5][6][7][8][9][10]. Sn introduction slows down the natural ageing process of 6000 Al alloys, thus helping in keeping the alloy stable during the transportation period from one place to another [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 10% of weight reduction in vehicle improves about 6-8% in the fuel efficiency [8,9]. Several high-strength and high-integrity Al-Si-Cu and Al-Mg-Si die-cast aluminum alloys have thus been developed for the automotive applications [10]. The increasing applications of lightweight Al-Si cast alloys lead to the development of novel or modified Al-Mg-Si alloys, since the inferior ductility and toughness of normal cast aluminum alloys failed to meet rigorous requirements of structural component subjected to cyclic stresses due to the existence of impurities and casting defects [11,12].…”
Section: Introductionmentioning
confidence: 99%